The Influence of Patient Positioning in Breast CT on Breast Tissue Coverage and Patient Comfort - Rößler, A. C.; Wenkel, E.; Althoff, F.; Kalender, W. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: The presented study aimed at optimizing a patient table design for breast CT (BCT) systems with respect to breast tissue coverage and patient comfort. Additionally, the benefits and acceptance of an immobilization device for BCT using underpressure were evaluated.Materials and Methods: Three different study parts were carried out. In a positioning study women were investigated on an MRI tabletop with exchangeable inserts (flat and cone-shaped with different opening diameters) to evaluate their influence on breast coverage and patient comfort in various positioning alternatives. Breast length and volume were calculated to compare positioning modalities including various opening diameters and forms. In the second study part, an underpressure system was tested for its functionality and comfort on a stereotactic biopsy table mimicking a future CT scanner table. In the last study part, this system was tested regarding breast tissue coverage.Results: Best results for breast tissue coverage were shown for cone-shaped table inserts with an opening of 180 mm. Flat inserts did not provide complete coverage of breast tissue. The underpressure system showed robust function and tended to pull more breast tissue into the field of view. Patient comfort was rated good for all table inserts, with highest ratings for cone-shaped inserts.Conclusion: Cone-shaped tabletops appeared to be adequate for BCT systems and to allow imaging of almost the complete breast. An underpressure system proved promising for the fixation of the breast during imaging and increased coverage. Patient comfort appears to be adequate.Key points:• Tissue coverage in breast CT is highly dependent on patient table design.• An underpressure fixation system shows potential to increase breast coverage.• The proposed breast CT patient table design combines good coverage and patient comfort.Citation Format:• Rößler AC, Wenkel E, Althoff F et al. The Influence of Patient Positioning in Breast CT on Breast Tissue Coverage and Patient Comfort. Fortschr Röntgenstr 2015; 187: 115 – 122
Keywords: breast; CT; MR imaging